2018
DOI: 10.48550/arxiv.1807.00898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model-based Hand Pose Estimation for Generalized Hand Shape with Appearance Normalization

Jan Wöhlke,
Shile Li,
Dongheui Lee

Abstract: Since the emergence of large annotated datasets, state-of-the-art hand pose estimation methods have been mostly based on discriminative learning. Recently, a hybrid approach has embedded a kinematic layer into the deep learning structure in such a way that the pose estimates obey the physical constraints of human hand kinematics. However, the existing approach relies on a single person's hand shape parameters, which are fixed constants. Therefore, the existing hybrid method has problems to generalize to new, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Much of the progress made in hand pose estimation have focused on using depth image inputs [5,6,7,8,11,14,15,18,19,32,33,35]. State-of-the-art methods use a convolutional neural network (CNN) architecture, with the majority of works treating the depth input as 2D pixels, though a few more recent approaches treat depth inputs as a set of 3D points and or voxels [7,5,15].…”
Section: Hand Pose Estimationmentioning
confidence: 99%
“…Much of the progress made in hand pose estimation have focused on using depth image inputs [5,6,7,8,11,14,15,18,19,32,33,35]. State-of-the-art methods use a convolutional neural network (CNN) architecture, with the majority of works treating the depth input as 2D pixels, though a few more recent approaches treat depth inputs as a set of 3D points and or voxels [7,5,15].…”
Section: Hand Pose Estimationmentioning
confidence: 99%
“…Stereo input was similarly explored [24,40,47]. With the wide availability of commodity depth sensors around 2010, the research also focused on monocular depth or RGBD input [10,20,29,31,36,37,43,55,56,57,61]. However, shortly thereafter, the success of deep learning lead to the proliferation of robust systems that perform on monocular RGB input [3,4,9,11,13,17,22,34,41,48,53,54,58,62,63].…”
Section: Literature Overviewmentioning
confidence: 99%
“…The accuracy achieved with the availability of depth information yielded the first practical real-time systems [37], and enabled on-the-fly adjustment of the bone lengths to the observed hand [29,59]. The development and availability of a parametric hand pose and shape model [49] in turn fueled research towards estimating the surface of the observed hand [2,11,22,32,61]. Finally, some very recent works are presenting the first attempts to model the appearance of the hand to some extent [5,32,44].…”
Section: Literature Overviewmentioning
confidence: 99%